Deficits in Identification of Goals and Goal‐Concordant Care After Sepsis Hospitalization. Issue 11 (20th October 2021) - Taylor, Stephanie Parks; Kowalkowski, Marc A; Courtright, Katherine R; Burke, Henry L; Patel, Sangnya; Hicks, Samantha; Hurley, Cristina; Mitchell, Stephen; Halpern, Scott D
Abstract : In a recent study, identifying and supporting patients' care goals was named the highest priority in hospital medicine. Although sepsis is one of the leading causes of death and postdischarge morbidity among hospitalized patients, little is known about how frequently care goals are assessed prior to discharge and adhered to in the 90 days after sepsis hospitalization. Evaluating a cohort of 679 high‐risk sepsis survivors enrolled in a clinical trial, we found that care goals were documented explicitly in a standardized tool in 130 patients; an additional 139 patients were identified using all available clinical documentation, resulting in only 269 (40%) patients with goals that could be ascertained from the electronic health record (EHR). Among those categorized, goals were classified as prioritizing longevity (35%), function (52%), and comfort (12%). Based on expert review of the care provided during the 90 days subsequent to discharge, goal‐concordant care was identified in 184 (68%) cases for which goals were specified. Documentation of goals in a standardized EHR tool was associated with increased likelihood of receiving goal‐concordant care (odds ratio, 3.6; 95% CI, 2.4‐5.5). Hospitalization and peridischarge time points represent important opportunities to address deficits in the documentation of goals and provision of goal‐concordant care for sepsis survivors.